(untitled) (Baghdad Science Journal, 2019)
Aeromonas salmonicida is a fish pathogen and recognized to cause a variety of diseases in humans. There are a few information about A.salmonicida in Iraq and there is no any previous molecular study on it. During the period of December 2017 to May 2018; Sixteen isolates of the A. salmonicida were isolated and identified from 300 common carp (Cyprinus carpio) fishes stomach in aquarium of Erbil city/ Iraq by using manual, automated Vitek 2 compact system, and confirmed by PCR using gene TonB-dependent siderophore (364bp). Antimicrobial susceptibility was determined by disk diffusion method and the results found that all isolates 100% susceptible to imipenem, 100% resistant to nalidixic acid and variable resistance to other studied antibiotics. The antibacterial effect of aqueous and alcohol extracts of Eminium spiculatum was studied by MIC and Molecular studies. The results found that aqueous and alcohol extracts of E. spiculatum have inhibitory effect and the MIC were 1400, 1800 µg/ml respectively. The sub MIC was used for both plant extracts, in plasmid profile the number of plasmid DNA was differ when treated with plant extracts. The inhibitory effect of the plant extracts against total proteins was studied by SDS- polyacrylamide gel electrophoresis and the results showed that there were variations in the protein bands in studied isolates and induction of new bands after treating with plant extracts. It was concluded that the leaves extracts of E.spiculatum could be used as antimicrobial for treatment of A. salmonicida infections and the results were confirmed by molecular studies.